Urban connectivity in Johor Bahru City Center: a review study - Seron, Nor Fasihah Ngah; Hanapi, Nor Amalina; Wan Ismail, W. H. (Penerbit UTHM, 2021)
This paper will discuss the urban connectivity that relates to pedestrian movements within Johor Bahru City Centre. The study is about Johor Bahru that lose its liveliness as its urban connectivity has changed over time. There are places in the city center that have a significant value that are still disclose from the public. The traditional old shop houses existed at Johor Bahru has a lot to offer to the visitors if they are well maintain and fully utilized. Therefore, the study is conducted to identify the pedestrian movements and how it relates of creating a lively place. Besides that, the need of urban connectivity in Johor Bahru also will further discuss in this paper to discover the preferable type of pedestrian way by the user. The primary data collection is through literature review of related topics of urban connectivity and the significance of the site study and observation of pedestrian movements affecting the city center vibrancy as the secondary data collection. The findings show the positive and the negative relationship of pedestrian movement connections with the existing pedestrian infrastructure and how they can improve the urban connectivity to build a vibrant identity of Johor Bahru.